Utilizing DAW FL Studio as a Transformation of Traditional Music Learning to Digital Media - Ahsin Maulana; Hendro T.G Samosir; Andi Arie Astuti (Universitas Negeri Medan, 2026)
This study examines the pedagogical role of Digital Audio Workstation (DAW) in traditional music learning among students of the Music, Dance, and Drama Education Study Program at the University of Palangka Raya. The research aims to analyze the functions of digital media, the role of DAW in the learning process, student interactions, creative exploration, and the integration of traditional music into digital environments. A qualitative case study approach was employed involving 21 students enrolled in the Central Kalimantan Traditional Music course. Data were collected through participatory observation, semi-structured interviews, documentation of student arrangement projects, FL Studio project files, audio recordings, and field notes. Data were analyzed using an interactive model and thematic analysis. The findings reveal that FL Studio functioned as a medium for musical exploration, production, and evaluation by enabling students to repeatedly revise and refine their musical arrangements. The learning process was characterized by active collaboration, peer assistance, lecturer guidance, and reflective practice, indicating the presence of scaffolding and collaborative knowledge construction. Students demonstrated creative exploration through experimentation with rhythm, melody, layering, and instrumentation while adapting traditional musical elements into digital formats. The integration of traditional instruments such as Panting Dayak, Rebana, and Gong Dayak into digital arrangements further demonstrated the potential of DAW-based learning to support cultural preservation and revitalization. The study concludes that DAW functions not only as a music production tool but also as a pedagogical environment that facilitates creativity, learner autonomy, collaborative learning, and cultural sustainability in higher education traditional music learning contexts.